Association of Met/Val polymorphism of BDNF gene with Alzheimer's disease in Chinese patients: Met/Val polymorphism of BDNF gene in AD - Li, Xiuming; Tian, Peiyan; Hu, Xinmin (Cellular and Molecular Biology, 2022)
Alzheimer's is the most common cause of dementia in the elderly. In this disease, genetic and environmental factors are involved. In Alzheimer's, changes of nucleotide 196 (G> A) or valine polymorphism of 66-methionine in the BDNF gene is a risk factor for brain-derived neurogenic factors. In China, this polymorphism has not been studied in Alzheimer's patients and perhaps this study could provide appropriate information on the prognosis and susceptibility of the disease. Therefore, in this case-control study, 73 patients with Alzheimer's disease and 100 patients as a healthy control group were studied. Blood samples were taken from the mentioned individuals and DNA was extracted. After quantitative and qualitative DNA analysis, a PCR-RFLP test was performed and the results of both groups were compared. The results showed that 14 patients and 7 people in the control group had BDNF gene polymorphism. In the patient group, the number of people with normal allele was 59. Heterozygous people were 8 and people with methionine/methionine alleles were 6. In the control group, 93 normal individuals, 5 heterozygous individuals, and 2 people had methionine/methionine alleles. In general, increasing the accumulation of valine/methionine polymorphism of the BDNF gene in Alzheimer's patients compared to control can indicate the role of this polymorphism. Clinically, patients with this polymorphism had a more unfavorable clinical condition compared to patients without it. Therefore, evaluation of the presence of this polymorphism can provide appropriate information about the disease status.